1966
DOI: 10.1136/jmg.3.2.129
|View full text |Cite
|
Sign up to set email alerts
|

An XO-X ring X chromosome mosaicism in an individual with normal secondary sexual development.

Abstract: The patient was referred for paediatric opinion because at the age of 13 years she was still only I25 cm. tall. However, her secondary sexual development was normal and she first menstruated shortly after her I3th birthday. After a few months without periods she began to menstruate regularly. Two buccal smears taken at this time failed to show sex chromatin, and it seemed possible, that despite her normal secondary sexual development and regular menstruation, she might have a sex chromosome abnormality. She wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Similarly, Dennis et al 119931 described 2 females with MR and r(X)s that were determined to be inactive by BrdU replication studies (cases 2 and 3) and XIST expression analysis (case 2). Possible explanations for these cases include 1) the X bodies formed by the r(X) in the case described by Tharapel et al were too small to be observed; 2) the r(X) in these cases differ in their genetic content from those in other cases; 3) the presence of a small percentage of active r(X)s in the cases reported by Dennis et al is sufficient for the manifestation of the observed atypical UTS phenotype; 4) these may truly be exceptional cases; or 5) the activity Guttenbach et al, 1991Johnson et al, 1991Tharapel et al, 1992Lin et al, 1990Crolla and Llerena, 1988Kushnick et al, 1987Rott et al, 1986de Grouchy et al, 1985Dennis et al, 1993Tharapel et al, 1992 UTS cases This study Zenger-Hain et al, 1992Tharapel et al, 1992Nagel et al, 1984Boczkowski et al, 1978Hagemeijer et al, 1976Picciano et al, 1972Bishop et al, 1966Luers et al, 1963Lindsten and Tillenger, 1962 Includes only marker or ring chromosomes which were definitively identified to be derived from an X chromosome and S G group chromosome in size. " I N D means the analyses were performed but the results were indeterminate.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Dennis et al 119931 described 2 females with MR and r(X)s that were determined to be inactive by BrdU replication studies (cases 2 and 3) and XIST expression analysis (case 2). Possible explanations for these cases include 1) the X bodies formed by the r(X) in the case described by Tharapel et al were too small to be observed; 2) the r(X) in these cases differ in their genetic content from those in other cases; 3) the presence of a small percentage of active r(X)s in the cases reported by Dennis et al is sufficient for the manifestation of the observed atypical UTS phenotype; 4) these may truly be exceptional cases; or 5) the activity Guttenbach et al, 1991Johnson et al, 1991Tharapel et al, 1992Lin et al, 1990Crolla and Llerena, 1988Kushnick et al, 1987Rott et al, 1986de Grouchy et al, 1985Dennis et al, 1993Tharapel et al, 1992 UTS cases This study Zenger-Hain et al, 1992Tharapel et al, 1992Nagel et al, 1984Boczkowski et al, 1978Hagemeijer et al, 1976Picciano et al, 1972Bishop et al, 1966Luers et al, 1963Lindsten and Tillenger, 1962 Includes only marker or ring chromosomes which were definitively identified to be derived from an X chromosome and S G group chromosome in size. " I N D means the analyses were performed but the results were indeterminate.…”
Section: Discussionmentioning
confidence: 80%
“…Other findings described in these 26 cases included significant growth retardation (22 cases) and unusual facial features (13 cases). In three cases with ring (X) chromosomes, a number of additional features were found such as relative hyperteloroid eye problems [Dennis et al 1993], hypothyroidism and glucose intolerance [Batch 2002;Sybert and McCauley 2004], heart abnormalities [Cohen et al 1967], seizures [Callen et al 1991], hypotonia [Buhler 2011], simian creases [Buhler 1980], and facial hemangiomata [Bishop et al 1966]. Cole and colleagues [1994] reported four cases with mosaicism levels varying from 70% to 16% and karyotypes of 45,X/46,X,+r.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of XO cells by secondary loss of the ring leads to XO/XXR mosaicism and consequently a significant proportion show features of Turner's syndrome (Bishop et al, 1966). The ovaries were only examined in one patient (Lindsten and Tillinger, 1962) and were found to be hypoplastic with reduced numbers of primordial follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Ring X chromosomes appear to be equally rare, the only seven patients recorded having an XO/XXR configuration (Lindsten and Tillinger, 1962;Luers, Struck, and Nevinny-Stickel, 1963;Hustinx and Stoelinga, 1964;Pfeiffer and Buchner, 1964;Fisher, 1965;Bain, Gauld, and Farquhar, 1965;Bishop, Blank, Simpson, and Dewhurst, 1966). Most of them showed features of Tumer's syndrome.…”
mentioning
confidence: 98%